An observed rise in γ-hydroxybutyrate-associated deaths in London: Evidence to suggest a possible link with concomitant rise in chemsex. (January 2017) - Hockenhull, Joanna; Murphy, Kevin G.; Paterson, Sue
Highlights: Reported data shows an increase in γ-hydroxybutyrate-associated deaths in London. Data suggests deaths are disproportionally high compared to use. Evidence is reported to suggest a possible link with concomitant rise in chemsex. Gamma-hydroxybutyrate-associated deaths are likely to be under-reported. Abstract: Background: Gamma-hydroxybutyrate (GHB) is the drug most linked to acute harm out of those used in chemsex, the incidence of which is reported to be increasing. However, there have been few systematic studies of the harms associated with GHB use. We investigated GHB-associated deaths from London coroners' jurisdictions between 2011 and 2015. Methods: Blood and urine samples were collected by pathologists and submitted for toxicological analysis at the request of coroners. Data from the Toxicology Unit, Imperial College London was retrospectively analysed. This comprised of 6633 cases from seven out of eight coroners' jurisdictions in London that underwent toxicological analysis between January 2011 and December 2015. Results: A total of 61 GHB-associated deaths (0.92% of total cases), 184 cocaine-associated deaths (2.8% of total cases) and 83 MDMA-associated deaths (1.3% of total cases) were identified. There was a 119% increase in the proportion of GHB-associated deaths detected in 2015 compared to 2014. Over the same time period there was a 25% increase in cocaine-associated deaths and a 10% decrease in MDMA-associated deaths. Conclusions: Our data suggest that GHB-associated deaths are increasing in London, and that this is likely at least in part due to increasing use of GHB for chemsex. Further studies on the use of GHB are urgently required to understand the extent of its use, whether this is as prevalent in other major urban areas in the UK, and the full extent of the harms it causes.